Internet influence on materialism among urban muslim women: Some challenges to the ummah - Wok, Saodah; Abdullah, Kalthom (2011)
Internet use is fast penetrating into the lives of urban women. The Internet can also influence materialism, due to the gratification of the medium, on the urban Muslim women in Malaysia. As such, this study tries (1) to explore the users of the Internet among urban Muslim women in Malaysia; (2) to determine the amount of money spent on selected material possession; (3) to examine the level of dependency on and skills in, usage, believability, and influence of the Internet; (4) to determine level materialism among urban Muslim women; (5) and to study the relationships between the Internet related variables and materialism among urban Muslim women. The theory used for the study is Cognitive Dissonance Theory (Festinger, 1957). A total of 357 Malay urban women participated in the study. Data were collected through survey research design using questionnaire as the instrument of the study. Data was analyzed using SPSS WIN 16 to answer the objectives of the study and to test the hypotheses postulated.